Gluten intake and risk of celiac disease: Long-term follow-up of an at-risk birth cohort - Mårild, Karl (Am J Gastroenterol, 2019)
OBJECTIVE: To determine the association between the amount of gluten intake in childhood and later celiac disease (CD), for which data are currently scarce. METHODS: The prospective DAISY cohort includes 1875 at-risk children with annual estimates of gluten intake (grams/day) from age one year. From 1993 through January 2017, 161 children were, via repeated tissue transglutaminase (tTGA) screening, identified with CD autoimmunity (CDA, persistent tTGA positivity); of these, 85 children fulfilled CD criteria of biopsy-verified histopathology or persistently high tTGA levels. Cox regression, modeling gluten intake between ages one and two years (i.e., in one-year-olds), and joint modeling of cumulative gluten intake throughout childhood, were used to estimate hazard ratios adjusted for confounders (aHR). RESULTS: Children in the highest third of gluten intake between the ages of one and two years had a 2-fold greater hazard of CDA (aHR 2.17; 95%CI, 1.22–3.88; P-value=0.01) and CD (aHR 1.96; 95%CI, 0.90–4.24; P-value=0.09) than those in the lowest third. The risk of developing CDA increased by 5% per daily gram increase in gluten intake (aHR 1.05; 95%CI, 1.00–1.09; P-value=0.04) in one-year-olds. The association between gluten intake in one-year-olds and later CDA or CD did not differ by the child’s HLA genotype. The incidence of CD increased with increased cumulative gluten intake throughout childhood (e.g., aHR 1.15 per standard deviation increase in cumulative gluten intake at age six; 95%CI, 1.00–1.32; P-value=0.04). CONCLUSIONS: Gluten intake in one-year-olds is associated with the future onset of CDA and CD in children at risk for the disease.